The Carbon Absorption Value of Bruguiera gymnorrhiza in the Coastal Area of Dulupi Village, Boalemo District - Ilyas H. Husain; Abubakar Sidik Katili (Jurnal Biologi Tropis, 2023)
Carbon dioxide (CO2) levels in nature are increasing along with the development of human civilization. Mangrove forests can absorb and store carbon in large quantities and a long time so that it can become a strategy in mitigating climate change. This study aims to determine the Carbon Absorption Value of Above Surface Bruguiera gymnorrhiza in the Dulupi Coastal Mangrove Area, Boalemo Regency. This research is a quantitative descriptive study by measuring the density of Bruguiera gymnorrhiza mangrove vegetation using the distance method (Point-Centered-Quarter-Method). The density value of the mangrove species Bruguiera gymnorrhiza found in the coastal area of ​​Dulupi Village, Boalemo Regency is 12.49 trees/ha with an average distance of 11,231 m/tree. The calculation results of the total stem biomass value obtained from the sum of each individual Bruguiera gymnorrhiza mangrove biomass obtained a value of 12,251.37 Kg. The carbon absorption content in the leaves of the mangrove species Bruguiera gymnorrhiza in the coastal area of ​​Dulupi Village, Boalemo Regency, from all sample trees was 449.26 kg C/cm2 with an average carbon content of each sample tree's leaves of 17.97 kg C/cm2. So that the total carbon absorption potential of the stems and leaves of the Brugueira gymnorrizha mangrove species is 12,700.63 kg C/cm2.